2015
DOI: 10.1016/j.nicl.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive grip force is modulated by subthalamic beta activity in Parkinson's disease patients

Abstract: IntroductionHealthy subjects scale grip force to match the load defined by physical object properties such as weight, or dynamic properties such as inertia. Patients with Parkinson's disease (PD) show an elevated grip force in dynamic object handling, but temporal aspects of anticipatory grip force control are relatively preserved. In PD patients, beta frequency oscillatory activity in the basal ganglia is suppressed prior to externally paced movements. However, the role of the subthalamic nucleus (STN) in ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Beta power was also found to be decreased with increased task complexity just prior to movement (24). Imbach et al demonstrated beta band desynchronization during the execution of two different motor tasks (grip vs press) when assessing the event related potential 250 ms prior to and after the task (11). Furthermore, Fischer et al recently demonstrated a reduction in beta power during imagined levels of grip strength when assessed over a four second epoch (7).…”
Section: Discussionmentioning
confidence: 99%
“…Beta power was also found to be decreased with increased task complexity just prior to movement (24). Imbach et al demonstrated beta band desynchronization during the execution of two different motor tasks (grip vs press) when assessing the event related potential 250 ms prior to and after the task (11). Furthermore, Fischer et al recently demonstrated a reduction in beta power during imagined levels of grip strength when assessed over a four second epoch (7).…”
Section: Discussionmentioning
confidence: 99%
“…As control tasks, all patients performed several self-initiated movements during wakefulness (repetitive self-paced shaking and pressing movements) measured by an inertial measurement unit as described previously (Imbach et al, 2015). As a second control experiment, we identified movements during NREM sleep.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the two main therapeutic strategies, the administration of l -Dopa 3 , 9 and high-frequency DBS 8 , 10 , both lead to a suppression of beta-synchronicity in the STN. Beta-oscillations show fast and movement-dependent modulation over time 11 , 12 and have been proposed as a feedback signal to control the delivery of DBS in a closed-loop system 13 .…”
Section: Introductionmentioning
confidence: 99%